Development and Validation of a Cross-Nationally Stable Scale of Consumer Animosity - Hoffmann, Stefan; Mai, Robert; Smirnova, Maria (Journal of marketing theory and practice, 2011)
The paper suggests a measurement of consumer animosity that is applicable to respondents from different home countries and to different target countries of animosity. The multidimensional scale is based on the distinction of three universal drivers that mediate the influence of specific causes on general animosity: perceived threat, antithetical political attitudes, and negative personal experiences. By means of partial least squares, two studies validate the scale demonstrating (1) cross-national stability, (2) criterion validity (animosity influences product-specific country-of-origin images, boycotting, and purchase intention), and (3) construct validity (animosity is embedded in a nomological network of ethnocentrism, patriotism, and cosmopolitanism).